Extraparenchymal Opacities at Thoracic Imaging: Clues to an Unusual Etiology. Issue 3 (May 2015) - Sparacino, Nick; Thomas, Allen; Mand, Jasminder W.; Gotway, Michael B.; Sparacino, Jeffrey L.
Abstract : Abnormal opacities detected at chest radiography must be localized as parenchymal or extraparenchymal to facilitate differential diagnosis. Extraparenchymal opacities may arise from the chest wall soft tissues, osseous structures, or pleura. Regarding the latter, pleural effusion and fibrothorax are commonly recognized patterns of pleural disease encountered at thoracic imaging. Less commonly, nodules or masses arising from the pleura may be seen, and usually this imaging pattern reflects the presence of pleural malignancy. However, there are rare conditions that may affect the pleura and simulate malignant pleural disease, particularly thoracic splenosis. Splenosis represents autotransplantation of functional splenic tissue into ectopic sites, most frequently within the abdomen, and rarely the thorax. Splenosis usually results from episodes of thoracoabdominal trauma or following splenectomy, and may reach the left thorax, implanting on the left-sided pleura, when diaphragmatic injury is also present. Thoracic splenosis is most often detected asymptomatically by imaging performed for incidental reasons. The condition typically presents with left-sided pleural nodules or masses, which may enhance profoundly following intravenous contrast administration at thoracic CT, thereby simulating malignant pleural disease. If imaging manifestations or historical evidence of previous thoracic trauma are found, the diagnosis may be suspected, but often such is lacking as the enticing event has long been forgotten by the patient. Therefore, a high index of suspicion for thoracic splenosis must be maintained when left-sided pleural lesions suggesting pleural malignancy are encountered. The diagnosis of thoracic splenosis may be confirmed noninvasively with nuclear medicine techniques.